2021
DOI: 10.1162/dint_a_00095
|View full text |Cite
|
Sign up to set email alerts
|

OpenKG Chain: A Blockchain Infrastructure for Open Knowledge Graphs

Abstract: The early concept of knowledge graph originates from the idea of the Semantic Web, which aims at using structured graphs to model the knowledge of the world and record the relationships that exist between things. Currently publishing knowledge bases as open data on the Web has gained significant attention. In China, CIPS(Chinese Information Processing Society) launched the OpenKG in 2015 to foster the development of Chinese Open Knowledge Graphs. Unlike existing open knowledge-based programs, OpenKG chain is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…OpenKG [14] , an open resource-sharing platform for knowledge graphs, includes a collection of 275 open-source projects that contribute to knowledge graph construction. Drawing inspiration from relevant content in these projects, valuable insights can be gained for the construction of an ontology library.…”
Section: Reuse Of Existing Related Ontologiesmentioning
confidence: 99%
“…OpenKG [14] , an open resource-sharing platform for knowledge graphs, includes a collection of 275 open-source projects that contribute to knowledge graph construction. Drawing inspiration from relevant content in these projects, valuable insights can be gained for the construction of an ontology library.…”
Section: Reuse Of Existing Related Ontologiesmentioning
confidence: 99%
“…The former can be used to enhance the querying and reasoning capabilities of the BlockChain where the latter is used mostly to keep the knowledge graphs privacy, trust and security by making it protected and decentralized. The merging of these two technologies has been supported in recent years due to their success in many domains like data sharing [10] and recommendation systems [11].…”
Section: Knowledge Graph Privacy and Blockchainmentioning
confidence: 99%
“…Graph is a prevalent model to represent entities (i.e., nodes) and their relationships (i.e., edges) in many of today's real-world information networks [56,16,47,34,7], e.g., social networks, collaboration networks, and criminal networks. For example, authors in a collaboration network are represented as nodes and the co-authorship between authors is indicated by an edge.…”
Section: Introductionmentioning
confidence: 99%